Academic Genre Processing Strategies Among Tertiary Esl Readers - Latih, Hafizah (2009)

(untitled)
In recent years, the genre-based approach has progressively made inroads into English for Specific Purposes (ESP) and in particular English for Academic Purposes (EAP) research and practice to meet the learners‟ communicative needs. This study examined the reading processes of a selected group of tertiary students majoring in English Language Studies when reading a research article (RA) in their discipline of study. Using a case study method sited within the exploratory-interpretive paradigm, the present study qualitatively looked into the reading behaviours of six ESL readers with average command of the language while engaging with the RA vis-à-vis the strategies they utilized to comprehend the RA. The study also probed the readers‟ rhetorical awareness of the RA genre, the reading problems they faced, and how these factors have shaped their reading behaviours. Data were gathered via several instruments i.e., text-labelling and sequencing tasks, reading comprehension task, written recall task, think-aloud protocols, and retrospective interview. To complement the qualitative data, two surveys were conducted using the Revised Approaches to Studying Inventory (RASI) and the Metacognitive Awareness (MCA) questionnaire involving 42 final year ELS students. The RASI was employed to examine the extent to which the subjects utilized certain approaches to their studying i.e., whether they employed a „surface‟ or „deep‟ approach in coping with their study tasks. The MCA was used to measure the students‟ perceptions about their metacognitive awareness when reading academic texts in the second language (L2). The qualitative analysis revealed that the readers‟ dependence on „local‟ or „bottomup‟ processing strategies had negatively affected their understanding of the RA and hence, their overall reading task performance. Results also indicated that their reading problems were probably caused by the presence of difficult words combined with the syntactic complexity peculiar to research genre in question as well as their unfamiliarity with research terminology. They generally seemed to possess some awareness of the rhetorical structure of the RA but their lack of understanding of the workings of this genre had quite clearly affected their comprehension and overall task performance. In the quantitative part of this study, the RASI survey indicated the students‟ relatively low academic self-confidence and a high tendency to adopt the „surface‟ rather than the „deep‟ approach in their learning. Analysis of the MCA responses revealed the students‟ equally low confidence levels when reading specialized academic text in the L2. Consequently, they were more inclined to use the „local‟ strategies when reading the RA. The findings of the study call for the implementation of an ESP/EAP genre-based framework in reading instruction to meet the readers‟ academic reading needs more effectively. Interventionist measures in the form of metacognitive strategy training and rhetorical consciousness-raising in L2 reading are equally crucial in that the students can be trained to read like the more expert readers of the disciplinary community. Students should also be given guidance on the proper approaches to studying while at the university so that their study practices are consistent with the aims of higher education.